Laughter and its role in the evolution of human social bonding - Dunbar, RIM (Royal Society, 2022)
In anthropoid primates, social grooming is the principal mechanism (mediated by the central nervous system endorphin system) that underpins social bonding. However, the time available for social grooming is limited, and this imposes an upper limit on the size of group that can be bonded in this way. I suggest that, when hominins needed to increase the size of their groups beyond the limit that could be bonded by grooming, they co-opted laughter (a modified version of the play vocalization found widely among the catarrhine primates) as a form of chorusing to fill the gap. I show, first, that human laughter both upregulates the brain's endorphin system and increases the sense of bonding between those who laugh together. I then use a reverse engineering approach to model group sizes and grooming time requirements for fossil hominin species to search for pinch points where a phase shift in bonding mechanisms might have occurred. The results suggest that the most likely time for the origin of human-like laughter is the appearance of the genus Homoca 2.5 Ma.